A high-fat diet exacerbates arsenic toxicity in various organs. A systematic review of toxicity and mechanism - Hoda Vahedi; Fateme Pourmotahari; Ali Akbar Oroojan; Amin Rasekhian; Soheila Alboghobeish (Current Research in Toxicology, 2025)
Background: Arsenic contamination in drinking water remains a primary global health concern. Recent evidence indicates that dietary habits, especially high-fat diets, may exacerbate arsenic-induced toxicity. This systematic review examines the impact of high-fat diets on arsenic toxicity across various organs and investigates the mechanisms underlying this interaction. Methods: A comprehensive literature search was conducted in PubMed, Scopus, Web of Science, and Embase databases. Studies involving animal models exposed to both arsenic and high-fat diets were included in this analysis. The methodological quality of the studies was assessed using the SYRCLE risk of bias tool. Results: A total of 20 studies met the inclusion criteria. High-fat diets were found to increase arsenic bioavailability and intensify oxidative stress in several organs, including the brain, heart, testes, and kidneys. Combined exposure to arsenic and high-fat diets resulted in complex metabolic disturbances, including impaired fatty acid metabolism in adipose tissue and a unique diabetogenic effect characterized by glucose intolerance without the typical features of type 2 diabetes. Interestingly, this combination also caused reduced weight gain despite increased insulin resistance and β-cell dysfunction. Modulation of hepatic autophagy pathways emerged as a possible mechanism linking arsenic toxicity to metabolic dysregulation. Conclusions: This review highlights that high-fat diets amplify arsenic toxicity through several mechanisms, including increased bioavailability, elevated oxidative damage, and altered metabolic signaling. The synergistic effects on glucose regulation and multi-organ toxicity underscore the importance of considering dietary habits in assessing arsenic-related health risks. Further research is warranted to clarify the molecular mechanisms involved and to design targeted strategies for mitigating arsenic toxicity, particularly in populations consuming high-fat diets.